The Securitization of Society: On the Rise of Quasi-Criminal Law and Selective Exclusion - Schuilenburg, Marc (Social justice, 2011)
The article looks at systems of law, law enforcement, and safety promotion as of 2011, discussing the advent of what the author terms quasi-criminal law, or the use of civil law agreements involving parties other than police and government officials, for instance shopkeepers, to define and prevent offensive conduct. He outlines a program adopted in several cities in the Netherlands, the "Collective Shop Ban," designed to prevent shoplifting as well as other antisocial behavior that may not be illegal in downtown shopping areas. He explores the meaning of such programs through the lens of philosopher Michel Foucault's concept of "sécurité" as developed in his 1978-1979 lectures "Sécurité, territoire, population" and "Naissance de la biopolitique."